COMMENTARY: Reply by Hansen and Lieberman Effects Resembling a Bio-field on a Torsion Pendulum Cannot be Caused by Heated Air Currents Generated by the Subject - Hansen, John Norman (Journal of Scientific Exploration, 2015)
<!–[if gte mso 9]> 14.00 <![endif]–> This paper is a reply to the paper: “Is the human bioenergy field detected by a torsion pendulum? The effect of shielding and a possible conventional explanation,” W. H. van den Berg and W. G. van der Sluys, Journal of Scientific Exploration, submission in progress. The latter paper was inspired by “Use of a Torsion Pendulum Balance to Detect and Characterize What May be a Human Bioenergy Field,” J. N. Hansen and J. A. Lieberman, Journal of Scientific Exploration, Vol. 27, No. 2, pp. 205–225, 2013. Throughout this current paper, we will use abbreviations to refer to our and the van den Berg paper. Accordingly, the van den Berg/van der Sluys paper will be abbreviated as vdB, and the Hansen/Lieberman paper will be abbreviated H&L. To facilitate access to the H&L paper, it is available at: http://hdl.handle.net/1903/15607 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>